Aplikasi Interaktif Mengenai Semut Jepang Sebagai Obat Alternatif berbasis Flash - Putra, Yan Ivan Handana; Santoso, Leo Willyanto; Handojo, Andreas (Jurnal Infra, 2016)
Healthiness is one of great treasure for human. we all love and seek healthiness. but sometimes we have no power against illness, we have no money for all the medical treatment. one of the way to cure illness is through alternative treatment.This application will show an alternative treatment with a tutorial to consume japanese ant with measure table for some illness, and a tutorial to raise japanese ant. There is also mini game to relieve your boredom.From many testimonies by friends and family, japanese ant can really cure some illness. This method can be used for people who donât have enough money to afford medical treatment.